Effect of age, gestation and lactation on faecal IgA and calprotectin concentrations in dogs*. (30th September 2014) - Grellet, Aurélien; Mila, Hanna; Heilmann, Romy M.; Feugier, Alexandre; Gruetzner, Niels; Suchodolski, Jan S.; Steiner, Jorg M.; Chastant-Maillard, Sylvie
Abstract: Faecal calprotectin and IgA have been suggested as non-invasive markers of gut health. Faecal calprotectin is a marker of intestinal inflammation in adults, whereas IgA has been suggested as a marker of intestinal immunity. The purpose of the present study was to evaluate the effect of gestation, lactation and age on faecal concentrations of these biomarkers. Thirty puppies, nineteen pregnant or lactating bitches and eighty-nine healthy control adult dogs were included in the study. Faeces were collected from the fourth week of gestation until the eighth week of lactation in pregnant and lactating bitches, and between 4 and 9 weeks of age in puppies. Faeces from the eighty-nine healthy control adult dogs were also collected. Faecal calprotectin and IgA concentrations were measured. Faecal calprotectin concentrations in control dogs were significantly lower than faecal calprotectin concentrations in puppies between 4 and 6 weeks of age ( P  < 0·001) or between 7 and 9 weeks of age ( P  = 0·004). Puppies between 4 and 6 weeks of age had significantly higher faecal IgA concentrations compared with puppies between 7 and 9 weeks of age ( P  = 0·001). Bitches during their second month of lactation had significantly lower faecal IgA concentrations compared with their first month of lactation ( P  = 0·049). Faecal calprotectin and IgA have been suggested as non-invasive and easily measured biomarkers of gut health in adults. However, the present study underlines that faecal IgA and calprotectin concentrations vary markedly depending of physiologic factors such as gestation, lactation and age. These factors need to be considered when these faecal biomarkers are used for evaluation of intestinal immunity or inflammation.